PERANCANGAN PROGRAM APLIKASI PENGENALAN TEKS MENGGUNAKAN FUZZY LOGIC - Ngarap Im Manik (Seminar Nasional Informatika (SEMNASIF), 2010)
This paper discusses application program design for character recoqnition with size font that medley to maximize accuration. Image processing method usually with used that is grayscaling, thresholding, filtering, segmentation, and streching. To the effect of method that is subject to be update image so as simple. This paper approach character recoqnition with use fuzzy logic. By marks sense this approaching, fonts on text can be recognized one about one bases characteristic that its proprietary. Output programs that resulting as text that readily been processed more and of examination that is done, letters recoqnition system one by one have accuration as 96,67%. on standard document recoqnition, increase that accuration resulting as big as 96,13%.